Choroidal Thickness Analysis in Patients with Usher Syndrome Type 2 Using EDI OCT - L. Colombo; B. Sala; G. Montesano; C. Pierrottet; S. De Cillà; P. Maltese; M. Bertelli; L. Rossetti (Journal of Ophthalmology)
To portray Usher Syndrome type 2, analyzing choroidal thickness and comparing data reported in published literature on RP and healthy subjects. Methods. 20 eyes of 10 patients with clinical signs and genetic diagnosis of Usher Syndrome type 2. Each patient underwent a complete ophthalmologic examination including Best Corrected Visual Acuity (BCVA), intraocular pressure (IOP), axial length (AL), automated visual field (VF), and EDI OCT. Both retinal and choroidal measures were measured. Statistical analysis was performed to correlate choroidal thickness with age, BCVA, IOP, AL, VF, and RT. Comparison with data about healthy people and nonsyndromic RP patients was performed. Results. Mean subfoveal choroidal thickness (SFCT) was 248.21±79.88 microns. SFCT was statistically significant correlated with age (correlation coefficient −0.7248179, p<0.01). No statistically significant correlation was found between SFCT and BCVA, IOP, AL, VF, and RT. SFCT was reduced if compared to healthy subjects (p<0.01). No difference was found when compared to choroidal thickness from nonsyndromic RP patients (p=0.2138). Conclusions. Our study demonstrated in vivo choroidal thickness reduction in patients with Usher Syndrome type 2. These data are important for the comprehension of mechanisms of disease and for the evaluation of therapeutic approaches.